The TPACK Approach Improves Student Collaboration Skills in 21st-Century Learning - Lutfiana, Rose Fitria; Nurul Zuriah; Saputri, Dinda Khairun Nisak (Universitas Pendidikan Ganesha, 2023)
21st-century education requires teachers to develop the 6C aspects of students, character, citizenship, critical thinking, creativity, collaboration, and communication. This study aims to analyze the effect of the TPACK approach on student collaboration in Civics subjects at school. This research uses quantitative research methods. The population in this study were seventh-grade junior high school students, totaling 178 students. Sampling in the study was carried out using a quota sampling technique with a final sample size of 75 students. Data collection in the study was carried out using non-test techniques, with research instruments in the form of questionnaires or questionnaires distributed via Google Forms. The data obtained in the study were then analyzed using quantitative descriptive analysis techniques through normality tests, linearity tests, and simple linear regression. The research analysis showed that the TPACK approach's influence on students' collaboration skills obtained a correlation coefficient of 0.592 with a contribution value of 35.1%. These results then show a significant influence between the TPACK approach and the collaboration skills of students in junior high school.